PENERAPAN PENDIDIKAN KARAKTER DI MTsN MEUREUBO - Kurniawan, Ade (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2021)
The reality of adolescent moral decadence in the current era is a serious problem that must be addressed immediately. In general, many problems are caused by a lack of character building. Because of that, character education is very important to be instilled. The role of schools as formal educational institutions is needed to continue to build the character from an early age through the application of good and quality character education and proper management. The purpose of this study was to find out how character education was applied at MTsN Meureubo Aceh Barat. This study uses a qualitative descriptive approach with data collection techniques in the form of observation, interviews, and documentation. The subjects of this research are stakeholders at MTsN Meureubo. The results of this study indicate that the process of implementing character education at MTsN Meureubo is carried out with four alternative strategies including being integrated into all subjects, into daily activities, into school programs, and building communication with parents of students.